Newman Error Analysis Siswa Madrasah dalam Menyelesaikan Soal Cerita Matematika - Marni Zulyanty (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
Students’ mistakes in solving the mathematical word problem is still a problem so it must be identified for each stage of solving. It is done so that the solutions offered are more effective. One way to identify the stage of solving of mathematical problem is the Newman Error Analysis stage. So the purpose of this research is to describe the ability of students of Islamic Junior High School to solve mathematical problems in the form of word problem and to describe the mistakes of high-ability Islamic High School students in mathematical word problem based on Newman Error Analysis. The approach used is qualitative descriptive. The research subject is the high-ability in Islamic Junior High School of Jambi City. Students are asked to work on solving questions in the form of word problems. Then the student interviewed about the mistakes that were made when solving the word problems given for each of the stages. The results showed 56% of high-ability students encountered an error while solving the algebra operation and 44% of high-ability students encountered an error while solving Pythagoras theorem. As for the errors that occur in high-ability students if in the analysis based on the stage of Newman Error Analysis occurs at the stage of understanding the problem (comprehension) and the problem transformation (transformation). Of course, errors in the comprehension and transformation cause errors at a later stage so that the solution or answer found is worth wrong. Keywords: Error, Newman Error Analysis, Mathematical Word Problem.